(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) infection are the global public health challenge. Family members of the HBV and HCV infected patients have a high risk of exposure to many blood-borne diseases including Hepatitis B, and Hepatitis C viral infections as well. So the objectives of the present study was to see the seropositivity of HBV and HCV among the family members of chronically infected viral hepatitis patients. Materials and methods: This cross sectional descriptive study was conducted among 80 family members of 50 patients with chronic HBV and HCV infection. After ethical clearance and written consent, 1stdegree family members of those chronically infected hepatitis patients were explained about the objectives of the study and a standard questionnairewere introduced and recorded. Venous blood samples was taken from every participant with universal precautions and was tested by Enzyme Linked Immunosorbent Assay (ELISA) for Hepatitis B surface antigen, anti HCV. Data analysis was done later by SPSS. Results: Eighty (80) family members of HBV[45(90%)] and HCV[5(10%] positive cases were screened. Among the family member, male were 45(56.3%) and female were 35(43.8%) and male to male ratio 1.28:1. Total 23(28.8%)family members were vaccinated against HBV. HBsAg and Anti HCV screening status of the relatives revealed HBsAg and anti HCV was found positive in 4(5%) and 1(1.3%) cases respectively. Conclusion: Relatives of the HBV and HCV infected patients are also at risk. So they should take proper preventive measures and should be vaccinated. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 37-40